The Role of Women's Leadership in the Traditional Muslim Religious Movement (New Paradigm in PBNU Leadership 2022-2027) - Arifi, Ahmad; Fathurrohman, Rizal (PALASTREN: Jurnal Studi Gender, 2023)
Seeing the structure of PBNU for the 2022-2027 Period, Gus Yahya (Top Leader of PBNU) gave an important role for women to join the structure of PBNU's daily management, after approximately 96 years PBNU did not involve women in its staff structure. This certainly affects the direction of PBNU organizational policies in the future. This study intends to analyze the shift in NU's religious paradigm related to the role of women in collective leadership at PBNU and its implications in responding to changing times as well as welcoming a new civilization within NU which is entering the second century. This research includes library research with a socio-phenomenological approach. This study resulted in the finding that the paradigm shift in NU leadership was based on changes in religious understanding and empirical experiences of NU clerics (Kiai and Nyai) in various aspects of life, religious, social, political, and cultural. In addition, many NU programs related to women such as reproductive health, sexual violence, migrant women workers, reproductive health, and women's radicalism are considerations for the importance of women's involvement in the development and implementation of these programs. Strategic roles in PBNU given to women such as Nyai Dr. (H.C) Sinta Nuriyah Abdurrahman at Musytasyar, Nyai Nafisah Ali Maksum at A'wan, Alissa Wahid and Khafifah Indar Parawansa at Tanfidziyah.